Investigation of the thermal effects of fuel injection into retained residuals in HCCI engine. (15th October 2018) - Hunicz, Jacek; Mikulski, Maciej
Graphical abstract: Highlights: Fuel injection into retained residuals offers enhanced HCCI controllability. Thermal effects of fuel reforming dominate over chemical effects. Fuel vaporization and oxidation provide different combustion control mechanisms. The role of exothermal reactions increases with the amount of excess air in the mixture. Abstract: Low-temperature combustion in reciprocating engines appears to be a cutting-edge technology which ensures extremely low emissions of nitrogen oxides and particulate matters in parallel with high fuel efficiency. This mode of combustion can be realized in homogeneous charge compression ignition engines. However, this technology poses challenges, and fast response combustion controllability is one of the issues to be solved to make this concept widely applicable. The introduction of direct injection of gasoline into recompressed residuals during negative valve overlap is one of the promising techniques to keep the advantages of having a homogeneous mixture during the main combustion while adding controllability through split ratio and injection timing within the recompression event. The present study aims to thoroughly investigate the thermal effects associated with gasoline injection during the negative valve overlap phase and explain qualitatively and quantitatively their impact on the gas exchange process and, further, on the combustion phasing during the main event. Single cylinder engine experiments are designed to evaluate these effects at different injection timings and mixture compositions. The scope of the research is focused on low-load operation at constant engine speed. The discussion of in-cylinder pressure analysis results and engine operational parameters is complemented by gas exchange simulations to provide more insight into the entire working process. It is confirmed by the results that negative valve overlap gasoline injection can be used as a measure to control combustion phasing in homogeneous charge compression ignition engines. The controllability is assured through balancing between evaporative cooling or heating of the trapped residuals. With this measure effective regulation of internal exhaust gas recirculation ratio, ranging from 41% to 64%, was demonstrated. This further enables fast intake valve closing temperature adjustment in a range of around 50 K, which finally results in superior auto-ignition timing control in a range between 5 °CA and 10 °CA before or after top dead center, depending on the global mixture strength. The work further provides fundamental understanding of the regulation mechanisms and concludes on the possibilities of applying this knowledge in a production engine.